2018
DOI: 10.1371/journal.pone.0205236
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive nest defence in ground-nesting birds and the risk of intermediate strategies

Abstract: Nest predation is an important determinant of reproductive success and ground-nesting birds exhibit a variety of nest defence strategies to mitigate the risk. Many small-bodied, ground nesting birds rely on deceptive behaviours such as injury-feigning to reduce nest predation: we call this behaviour active deception. However, active deception may entail risks to adults, and passive deceptive behaviour, where individuals effectively sneak away from the nest by flushing at long distances, may be an alternative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Moreover, the fact that sandpipers use distraction behaviour to divert predators from their nests (i.e. active deception; Gochfeld 1984, Montgomerie and Weatherhead 1988, Smith and Edwards 2018 also suggests that arctic predators are attracted to movements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fact that sandpipers use distraction behaviour to divert predators from their nests (i.e. active deception; Gochfeld 1984, Montgomerie and Weatherhead 1988, Smith and Edwards 2018 also suggests that arctic predators are attracted to movements.…”
Section: Discussionmentioning
confidence: 99%
“…Nests concealed by vegetation or other microtopography (e.g. hummocks) may be less likely to be located visually by predators, but the resulting obscured visibility for incubating adults may delay their departure when a predator is detected, which may both reduce the subsequent search area for the predator and put the incubating adult at risk of capture, although birds that flush at only short distances from predators are more likely to engage in injury‐feigning or other forms of active deception of the predator (Smith & Edwards 2018).…”
mentioning
confidence: 99%
“…When performing, the closer a parent is to a potential predator, and the more intense its display, the greater the risk compared with other behaviour (Brunton , Lima & Dill ), and so assessing predator proximity will be an important component of any decision to distract. Recently, Smith and Edwards () found that individual White‐rumped Sandpipers Calidris fuscicollis and Red Phalaropes Phalaropus fulicarius that flush from their nests at long distances in response to an approaching threat leave the vicinity of the nest immediately, whereas those that flush from close distances are more likely to engage in injury‐feigning. This latter strategy was associated with reduced risk of nest predation, but long‐distance flushing may be less common due to these birds' concealed nest‐sites (Smith & Edwards ).…”
Section: Trade‐offs and Alternative Tacticsmentioning
confidence: 99%
“…Recently, Smith and Edwards () found that individual White‐rumped Sandpipers Calidris fuscicollis and Red Phalaropes Phalaropus fulicarius that flush from their nests at long distances in response to an approaching threat leave the vicinity of the nest immediately, whereas those that flush from close distances are more likely to engage in injury‐feigning. This latter strategy was associated with reduced risk of nest predation, but long‐distance flushing may be less common due to these birds' concealed nest‐sites (Smith & Edwards ). Certainly, degree of nest concealment can be expected to influence individual variation in flushing distance and the co‐occurrence of additional defensive behaviours.…”
Section: Trade‐offs and Alternative Tacticsmentioning
confidence: 99%